Accounting for history in Marx's Capital the missing link - Bryer, Robert (Heterodox studies in the critique of political economy., 2019)
"The book reinterprets Marx's historical materialism as a world accounting history, answers his critics, and supports his theory with accounting evidence from history. It explains Marx's prediction of the inevitability of socialism, and outlines the necessary tasks of critical accounting for Marxists to get Day One"--